JFK. - Kitman Ho, A.,; Stone, Oliver,; Costner, Kevin,; Bacon, Kevin,; Lee Jones, Tommy,; Metcalf, Laurie,; Oldman, Gary,; Rooker, Michael,; Sanders, Jay O.,; Spacek, Sissy,; Williams, John, (Warner Home Video, 2001)
Las especulaciones sobre conspiraciones que podrían haber causado la muerte del presidente John Fitzgerald Kennedy